Быть любимой: роман / Людмила Белякова - Белякова Людмила Игоревна (Женские истории, 2004)
Экземпляры: Ф20 (20241223ԁ) / Инвентарный номер: 37872 / Цена: 19.50 / Сис.шифр: Р2 / Авт.знак: Б 44 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6